Global warming impairs the olfactory floral signaling in strawberry - Guaraci Duran Cordeiro; Stefan Dötterl (BMC Plant Biology, 2023)
Abstract Background Global warming is expected to impact the chemical communication between flowering plants and their pollinators. Surprisingly, it is unknown whether and how temperature-induced changes in scent emission affect pollinator behavior. Strawberry (Fragaria x ananassa) is a plant primarily pollinated by bees and hoverflies, with the former group being particularly attracted to the floral scent they emit. Results Using chemical analytical, electrophysiological, and behavioral approaches we tested whether temperature-induced shifts in floral scent of strawberry affect chemical communication with its main bee pollinators (Apis mellifera, Bombus terrestris, Osmia bicornis). While strawberry flowers in the optimum scenario released 10.4 ng/flower/hour, mainly p-anisaldehyde (81%) and seven other scent compounds, in the warmer scenario, the flowers did not emit any detectable scent. In the behavioral experiments, the pollinators were attracted by the scents of the optimum scenario. Conclusions We predict that the absence of detectable scent emissions from strawberry plants grown under heat stress will reduce the attractiveness of the flowers to the bee pollinators. Our study raises important ecological and agricultural questions, as decreased attractiveness of flowers to pollinators might potentially lead to insufficient bee pollination, with potential negative consequences for ecosystem functioning and crop yields, particularly in regions reliant on bees as primary pollinators. Given that our study centered on bee pollinators, it is needed to conduct further research to evaluate the impact on hoverflies.